An evaluation of the development of rural sanitation at Eisleben Village in Limpopo Province, South Africa - Molopa, Mamatsheu Bernard (University of Limpopo, 2008)
Rural sanitation researchers, particularly in the Limpopo Province, have not offered theories in relation to the patterns of the development of rural sanitation. Several researchers have concerned themselves with the need for the solution of water supply but not sanitation services. The present study seeks to enhance the understanding of the dynamics of the patterns of the development of rural sanitation in the Capricorn District Municipality, in particular at the Eisleben Village. This research paper applied an evaluative methodology to assess the impact of VIP sanitation technology at Eisleben Village at Ramokgopa under Capricorn District Municipality in Limpopo Province in comparison to dry sanitation. Supportive cases studies on sanitation delivery in South Africa have also been cited to where both technologies have been applied to assess their impact to the health and dignity of the communities, the environmental impacts. Examples of such case studies included examples of the Mosvold Hospital Sanitation Programme, the Northern Cape Household Sanitation Programme, the eThekwini Water and Sanitation Programme and the Dry sanitation in an urban environment at Weiler’s Farm in Johannesburg. The following five major findings emerged from the study: 1. Sanitation development should be community driven in terms of information, knowledge and decision making. 2. There is need for the vision of health, hygiene and education strategy for water and sanitation. Efficient and effective hygiene education is urgently needed. 3. There is resounding evidence from previous sanitation projects done in various places in South Africa that dry or waterless sanitation has been found to be an adequate sanitation technology that best suits urban, peri-urban and rural areas. 4. There is need to replace VIP with a better technology such as dry sanitation as a matter of urgency to avoid unhygienic and unhealthy conditions due to inadequate VIP sanitation technology. vii 5. Sanitation solution and technology should comply with the Department of Water Affairs and Forestry (DWAF) policies of adequate sustainable water and adequate sustainable sanitation solution, Millennium Development Goals (MDGs) and the German Helmhotz Association HFG’s “concept of integrated sustainable development”. In the main, the study suggests possible strategies and mechanisms to overcome the challenges that are identified in the research, with the idea in mind of contributing in improving sanitation, not only in the Eisleben Village, but rather to all rural communities in the Limpopo Province, South Africa.
Thesis (M.Dev.) --University of Limpopo, 2008
Keywords: Rural sanitation; Rural development; Sanitation, Rural -- South Africa; Rural development -- South Africa